Green HR Management Practices in Contemporary Business Organizations - Ali H. Al-inizi, Saad; A H. Al-dahhan, Iman (International Journal of Psychosocial Rehabilitation, 2020)
In order to achieve sustainable human development in the long run, emphasis should be placed not only on materials, equipment, and money but also on the social, environmental, and economic aspects of contemporary organizations work. Therefore, organizations have sought to use environmentally friendly green environmental management practices and initiatives to increase efficiency in operations, reduce environmental waste accumulation, reduce costs, waste recycling, identify tools and procedures to create green environmental behaviors for employees, and develop more efficient office space. At present, Green Human Resources Management is responsible for balancing labor and the environment to sustain the lives of talented and creative workers as valuable materials, equipment, and the industry as a whole. The research found that green human resource management plays a vital role in regulating environmental management issues and achieving sustainability for its members through the application of innovative clean technology that can reduce environmental degradation, seek renewable energy, reduce the use of limited natural resources, and create non-toxic products that do not pollute the environment.